195:poster Priority setting in Norwegian municipal health and care services: A content analysis of policy documents. (28th April 2022) - Torjusen, Marius L; Solberg, Carl Tollef; Barra, Mathias; Feiring, Eli
Abstract : Introduction: Norway has a long tradition of open priority setting in health care services. However, the principles and instruments for priority setting have mainly been used in specialist health care. In 2017, an official committee was commissioned to evaluate if and how to adopt the three Norwegian priority-setting criteria – health benefit, resources, and severity – in the municipal health and care services. The aim of this article was to examine the arguments for and against implementing the current criteria in municipal health and care services, using documentary data from the ensuing political process. Methods: Data consisted of Norwegian policy documents discussing prioritisation principles for municipal health and care services: The Official Norwegian Report 2018:6 (green paper), the written consultation responses from the hearings, and the Report to the Parliament 38 (2020-2021) (white paper). The documents were analysed using a predefined conceptual framework where arguments were categorised by their level of abstraction and the degree of (dis)agreement with the recommendations in the green paper. Results: Data suggested general agreement to use the same criteria in all levels of Norwegian health service. However, disagreement was identified when considering the lack of feasible implementation processes. Recurrent themes in the data were the municipalities' legal and financial lack of scope to set priorities under constraints, challenges regarding operationalising a supplementary physical, psychological and social mastery criterion, and prioritising in situations where the benefits are difficult to measure. Discussion: The many duties and responsibilities of municipal health and care make priority setting decisions more complex than in specialist health care. In summary, the Norwegian green paper on priority setting in municipal health and care services has presented a well-received recommendation. However, how to inevitably tackle the many complex, and sometimes wicked, prioritisation problems in practice remain unanswered.